Detection of Adulteration by Wedelia calendulacea in Eclipta alba through ISSR and RAPD Markers - Pendkar, Santhosh Kumar; Hegde, Satisha; Nayak, Shraddha Umesh; Hegde, Harsha; Kholkute, Sanjiva D.; Roy, Subarna (Planta Medica International Open, 2016)
In the crude herbal drug market, the highly medicinal Eclipta alba, popularly known as “Bhringaraja”, is often adulterated with Wedelia calendulacea. To evaluate the ability of simple genetic fingerprinting methods to differentiate between the two species, Inter-Simple Sequence Repeat and Random Amplified Polymorphic DNA assays were performed on 30 individuals of E. alba and 4 individuals of W. calendulacea. Samples of W. calendulacea were found to cluster in clades that distinctly separated from E. alba and at least one band was identified for each of the two species that can serve as a marker for identification. Despite wide variations and a limited number of samples, phylogenetic analysis helped in differentiating the original from the adulterant plant. The study underscores the importance of simple DNA-based fingerprinting as a cost-effective method for the detection of adulteration in plants, particularly with respect to E. alba.
Keywords: Eclipta alba; Wedelia calendulacea; Asteraceae; phylogenetics; adulteration; molecular markers